ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA PADA MATERI STATISTIKA DI KELAS VIII SMP - Marisyah Nungki Maulani; Lazira Azzahra; Reni Wahyuni (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This study intends to assess the extent to which grade VII junior high school students have mathematical literacy skills, especially in working on statistical problems that are directly related to daily life. In this case, mathematical literacy is defined as the ability of students to understand, analyze, and apply mathematical concepts to real and relevant situations. The method used in this study is a qualitative approach with a phenomenological focus, where as many as 29 students were made as the main participants. The data collection process was carried out using tests given to students as well as semi-structured interviews to dig deeper into their understanding and the obstacles they encountered while working on the questions. From the results of the analysis, it was found that there was a variation in the level of mathematical literacy ability among the students, with most of them classified in the medium to high category. Students who are in the high category show a fairly good mastery of concepts and are able to apply them appropriately. On the other hand, students who fall into the medium and low categories still face difficulties in solving problems and applying concepts regularly and systematically. These findings confirm that there is a need to improve the quality of mathematics learning, especially by emphasizing the understanding of concepts and the relevance of the material to daily life. In addition, it is also important to develop students' logical and analytical thinking skills so that they are better prepared to face various math problems.